2007
DOI: 10.1074/jbc.m609040200
|View full text |Cite
|
Sign up to set email alerts
|

Basic Fibroblast Growth Factor Stimulates Matrix Metalloproteinase-13 via the Molecular Cross-talk between the Mitogen-activated Protein Kinases and Protein Kinase Cδ Pathways in Human Adult Articular Chondrocytes

Abstract: Excessive release of basic fibroblast growth factor (bFGF) during loading and/or injury of the cartilage matrix may contribute to the onset or progression of osteoarthritis. This pathological role may be related to the ability of bFGF to decrease proteoglycan synthesis and to antagonize the activity of anabolic growth factors in cartilage such as insulin-like growth factor-1 and bone morphogenetic protein 7 (BMP7 or OP-1). Matrix metalloproteinase-13 (MMP-13), a catabolic cartilage-degrading enzyme, is dramati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
246
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 162 publications
(263 citation statements)
references
References 54 publications
16
246
1
Order By: Relevance
“…On the other hand, the results of inhibition by rottlerin or ⌬PKC-␦ on the mechanical straininduced p42/p44 MAPK phosphorylation suggested a mechanism of the molecular cross-talk between MAPK and PKC-␦ (30). In fact, we also found that cross-talk occurred between PDGFR-␣/PI3K and p42/p44 MAPK pathways.…”
Section: Volume 284 • Number 38 • September 18 2009mentioning
confidence: 47%
See 1 more Smart Citation
“…On the other hand, the results of inhibition by rottlerin or ⌬PKC-␦ on the mechanical straininduced p42/p44 MAPK phosphorylation suggested a mechanism of the molecular cross-talk between MAPK and PKC-␦ (30). In fact, we also found that cross-talk occurred between PDGFR-␣/PI3K and p42/p44 MAPK pathways.…”
Section: Volume 284 • Number 38 • September 18 2009mentioning
confidence: 47%
“…For example, the PKC-␦ activation is found to be a principle rate-limiting event in the basic fibroblast growth factor-dependent stimulation of MMP-13 in human articular chondrocytes (30), whereas the stimulation of the PDGFR-␤ signaling pathway activates PKC-␦ in the PDGFR-␤-mediated-monocytic differentiation (31). Furthermore, the stretch-induced expression of vascular endothelial growth factor appeared to be mediated by the PI3K/PKCpathway (32).…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence suggests that bFGF is pathologically associated with joint destruction via upregulation of MMPs and aggrecanases, as well as the stimulation of reactive oxygen species such as nitric oxide and superoxide anion (well-known catabolic factors for articular cartilage and spine discs), revealing the potential catabolic activity of bFGF in articular cartilage (Qu et al, 1995;Tchetina et al, 2005;Im et al, 2007;Muddasani et al, 2007, Muddasani et al, 2008. In patients with degenerative joint disease after traumatic injury, for example, the expression of bFGF is highly upregulated in synovial tissues of arthritic joints compared to normal joints (Cameron et al, 1994;Qu et al, 1995).…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 99%
“…Stimulation of human articular chondrocytes isolated from knee and ankle cartilage (both normal and OA) with bFGF was shown to upregulate MMP-13 and ADAMTS-4 and -5 expression (aggrecanases), inhibit PG production and synthesis in a time and dose-dependent manner, antagonize the activity of anabolic factors BMP7 and IGF-1, and stimulate pro-inflammatory cytokines such as IL-1 and TNF-α, elucidating the degradative effects of bFGF on articular cartilage homeostasis Im et al, 2008;Im et al, 2007;Muddasani et al, 2007). Others have reported similar findings in cultured human chondrosarcoma cells (Uria et al, 1998) and osteoblasts (Varghese et al, 2000), revealing that treatment with bFGF increases MMP-13 expression in a dose and time-dependent manner.…”
Section: Basic Fgf (A) Actions Of Bfgf In Articular Cartilagementioning
confidence: 99%
See 1 more Smart Citation